Morphological evolution of a barchan dune migrating past an offshore wind farm foundation. Issue 12 (26th July 2020) - Couldrey, Amelia J.; Benson, Thomas; Knaapen, Michiel A.F.; Marten, Kerry V.; Whitehouse, Richard J.S.
Abstract: As the number of manmade structures installed on the seafloor is increasing rapidly, we seek to understand the impact of these immobile obstacles on marine geomorphological processes, such as the evolution of bedforms. A 5.8 m diameter monopile foundation was installed at the case study offshore windfarm approximately 30 m ahead of an approaching barchan (crescent‐shaped) dune. The impact of the monopile on the dune's evolution was analysed using six multibeam bathymetry surveys spanning 20 years. To substantiate this analysis, coupled three‐dimensional numerical modelling of flows and sediment was conducted in which the scour inducing bed shear stresses were calculated from the modelled turbulent kinetic energy. Following the installation of the monopile, the mid‐section of the dune accelerated and stretched in the direction of the wake of the monopile. Four years after the monopile's installation the rest of the dune had caught up, flattening out the slip face within half the dune's length downstream of the monopile. Due to the modified flow field, the dune was scoured deeply at the base of the monopile to a depth of 6.8 m (supported by the model results that predicted a scour depth exceeding 2 m over a period of just a few days). The surveyed volume of material scoured amounted to 8% of the total dune volume. Whilst the process of scouring occurs at a timescale of days to weeks, the dune migrated on average by 25 m/yr. The difference in the timescale of the two processes allowed the scouring to occur through the full thickness of the dune. The scoured dune profile recovered rapidly once the dune migrated downstream of the monopile. This article demonstrates how large geomorphological features can intercept and migrate past a monopile foundation without long‐lasting impacts on the integrity of the feature or the foundation. © 2020 John Wiley & Sons, Ltd. Abstract : When an offshore wind farm foundation (monopile) was installed in the pathway of a solitary barchan dune the acceleration of the sand past the monopile caused a temporary stretching of the dune. Scouring at the monopile base took place through the complete thickness of the dune (> 5 m). The dune intercepted and migrated past the monopile without long lasting impacts on the integrity of the dune or monopile.